Coordinated Velocity Shift of Multiple C iv and Si iv Broad Absorption Lines in Quasar SDSS J113048.45+225206.6 - Wei-Jian Lu; Ying-Ru Lin (The Astrophysical Journal)
We present an analysis of the coordinated velocity shifts observed in multiple C iv and Si iv broad absorption lines (BALs) in the quasar SDSS J113048.45+225206.6. The quasar exhibits an extensive BAL system spanning a velocity range of approximately 13,000 km s ^−1 , which can be further delineated into five absorption systems (A1 to A5). Our analysis revealed coordinated velocity shifts in the C iv BALs of systems A1 and A2 and in the Si iv BALs of systems A2 and A3. These shifts were accompanied by coordinated variations in equivalent widths, which can be attributed to changes in the ionization state of the clouds in response to fluctuations in the ionizing continuum. By comparing the absorption line systems, we deduced that the velocity-shifted systems (A1 to A3) are located closer to the central engine, possess higher velocities, and are in a higher ionization state compared to the nonshifted systems (A4 to A5). These characteristics suggest that the outflow producing the velocity-shifted systems is situated in a more extreme environment and is more severely impacted by background radiation energy than the nonshifted systems. Furthermore, the synchronization of these velocity shifts across multiple components suggests a common underlying mechanism. Consequently, we infer that the coordinated velocity-shift signatures may indicate actual deceleration of the outflow clouds, driven by radiation pressure from the background light source.